Pendampingan Guru dalam Pemanfaatan Teknologi untuk Mengoptimalkan Pembelajaran Mendalam Menuju Pendidikan Bermutu - Wijayanti, Fitri; Miqawati, Alfi Hidayatu; Zuhro, Cholimatus; Susanti, Nila; Budi, Agus Setia; Aisyah, Siti; Yuwono, Shelsie Malini Putri (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance teachers’ competencies in utilizing technology to support deep learning in a public junior high school in Jember Regency. Deep learning requires students to think critically, creatively, and solve real-world problems; however, its implementation is often hindered by low digital literacy, limited technology and pedagogical skills, and inconsistent integration of digital tools in the classroom. The program was conducted on 14 and 18 October 2025 and involved 41 teachers. Data collection included observation, questionnaires, pre-tests, post-tests, and hands-on mentoring sessions. Pre-test results indicated an average score of 62.15, which increased to 84.63 in the post-test, demonstrating significant improvement in teachers’ ability to integrate technology into instruction. The mentoring activities effectively strengthened teachers’ digital literacy, pedagogical understanding, and practical skills in designing interactive and meaningful learning experiences. Overall, the program successfully supported teachers in adopting technology-enhanced deep learning aligned with the demands of 21st-century education.